2016
DOI: 10.1016/j.ecolecon.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Water consumption and subjective wellbeing: An analysis of British households

Abstract: While having basic access to water resources is clearly critical for survival, the extent to which water consumption contributes to wellbeing once basic needs have been met is not clear. In this study the link between household water consumption and wellbeing is assessed via a household survey conducted in southern England and actual water consumption data for the same households received from their water supply company. While the study revealed a few correlations, in general no link was found between actual w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A few have examined water use across multiple BTs within a single city (Chenowerth et al. 2016). In most cases, decreased total water use is attributed to a suspected reduction in outdoor water use as the number of DUUA increases (and thus the % pervious area decreases).…”
Section: Discussionmentioning
confidence: 99%
“…A few have examined water use across multiple BTs within a single city (Chenowerth et al. 2016). In most cases, decreased total water use is attributed to a suspected reduction in outdoor water use as the number of DUUA increases (and thus the % pervious area decreases).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of water consumption in the family was the highest when the family is composed of two young adults, and showed a downward trend when the average age of the family increased [16]. However, Chenoweth et al [17], in a survey in the UK, found that the number of adults, minors, and the total number of family members had a certain inhibiting effect on water consumption per capita, while the number of elderly people increased water consumption. In addition, studies by foreign scholars also show that population size is the main driving force for the increase in water consumption [18], and internationally recognized household consumption capacities and seasonal variations also need to be taken into account when assessing the water resource carrying capacity.…”
Section: Introductionmentioning
confidence: 98%
“…There is literature to support the idea that long-term cultural change can lead to habit development, leading to lower water consumption [3] especially in subjects with existing positive environmental awareness [4]. However, other literature such as [5]and [6] found there was no link between water use and environmental values or individuals' willingness to adopt water saving initiatives. This is despite [6] showing that households that consumed the least water exhibited higher levels of awareness of water conservation issues.…”
Section: Introductionmentioning
confidence: 99%
“…Although [7] found that there was a correlation between water use and the presence of technological utilization (dishwashers, washing machines etc.) in rural China, [5] and [8] state that in more developed regions, levels of domestic water use are more highly linked to the efficiency of the appliances installed as opposed to attempts to save water or concern for the environment. This is reinforced by regulations and standards which consider building water use a technological aspect, rather than occupant consideration [9].…”
Section: Introductionmentioning
confidence: 99%